Y chromosome diversity in a linguistic isolate (Mirandese, NE Portugal). Issue 5 (18th March 2016) - Marques, Sofia L.; Gusmão, Leonor; Amorim, Antonio; Prata, Maria João; Alvarez, Luis
Abstract : Objectives: The purpose of this study was to genetically characterize the male lineages of people who speak Mirandese, an interesting case of a linguistic relict that can still be found in the municipality of Miranda do Douro, NE Portugal. This region lies within the area of the Leonese dialects, which are remnants of the Romance dialects spoken in the Kingdom of Leon currently grouped in the Astur–Leonese linguistic continuum. We intended to disclose affinities with surrounding populations, namely from Spain where the Astur–Leonese is also spoken. Methods: Eighty‐eight unrelated males (58 from Miranda and 30 from Bragança, the broad Portuguese region where Miranda is located) were genotyped with the combined use of 17 Y chromosome short tandem repeats (Y‐STRs) and a high resolution Y chromosome single nucleotide polymorphism (Y‐SNPs) strategy. Moreover, 236 males from Miranda and neighboring regions, previously classified as R‐M269, were also genotyped. Results: R‐P312 was the most frequent haplogroup in the Mirandese, followed by J‐12f2.1 and T‐M70. The male lineages J‐12f2.1 and T‐M70 were also well represented, and both were shared with descendants of Sephardic Jews. No signs of diversity reduction were detected. Conclusions: Mirandese speakers display a Y chromosome gene pool that shows a subtle differentiation from neighboring populations, mainly attributable to the assimilation of lineages ascribed to be of Jewish ancestry. Although not revealing signs of geographic/linguistic isolation, no clear affinities with other Astur–Leonese populations were detected. The results suggest that in Miranda language sharing is not accompanied by significant gene flow between populations from both sides of the political border. Am. J. Hum. Biol. 28:671–680, 2016. © 2016 Wiley Periodicals, Inc.